Naïve Bayes Klasifikasi untuk Rekomendasi Strategi Promosi Tindakan pada Aesthetic Dental Clinic Karawang - Utami, Dwiarti Rahma; Kurniawan, Adi; Enri, Ultach (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
Aesthetic Dental Clinic is one of clinic in Karawang. To keep old patients and attract new patients visiting Aesthetic Dental Clinic, it is necessary to develop a new marketing strategy in promotion. The metodh of data mining classification can be used to help determine promotional strategies to attract customers. The Naïve Bayes algorithm can be helpful to predict customer interest based on promos given by the ADC Clinic (Aesthetic Dental Clinic). The Naïve Bayes algorithm is a data mining classification algorithm that can be used to support an effective and efficient promotion strategy. The result of this research is the application of the data mining algorithm, namely Naïve Bayes, which can provide important information such as prediction results in an effort to attract customer interest. The data used in this study is customer data from October 2020 - November 2020. The accuracy value generated by Naïve Bayes using Rapid Miner was 31.74% and the result of kappa value was 0.183. With the accuracy value obtained, it is hoped that it can help to support promotional strategies that have an impact on the effectiveness and efficiency of promotions and can increase the number of new customers.